The Effect of a Magnetic Field on the Enzymatic Activities of Common Airborne Aspergillus Strains Isolated from Indoor Environments - Anaya Villalpanda, Matilde (2025)
The aim of this study was to evaluate the effect of an extremely low-frequency oscillating magnetic field on the enzymatic activities of common airborne Aspergillus sp. strains that were isolated from indoor environments. A D-optimal experimental design with three factors was applied: magnetic field density (0.5 to 2 mT), exposure time (0.5 to 2 h), and Aspergillus sp. strains (A. ellipticus, A. japonicus, A. flavus, and A. fumigatus). The response variables were exoenzymatic indexes (cellulolytic, amylolytic, proteolytic, lipolytic, and hemolytic) and pH, as a measure of organic acid production. A. ellipticus was the highest producer of organic acids, and A. japonicus was as pathogenic as A. fumigatus. Different magnetobiological effects were observed: on enzyme secretion in the remaining strains, we detected no appreciable effect (Ilip and Iprot of A. flavus), inhibition (Ilip of A. ellipticus; Icel and Iamil of A. japonicus; Iamil and Iprot of A. fumigatus), and stimulation. Predictive quadratic models were obtained, and 2 mT for 2 h was the magnetic treatment regime that influenced the fungal enzymatic activity. These physiological changes following magnetobiological effects could be influenced during fungal sporulation andmust thus be considered in aeromicrobiology studies. They can also be beneficial for obtaining industrial-use enzymes, but detrimental to the biodeterioration of different materials and human health.